Biological Monitoring of Exposure to Benzene in Port Workers - De Maria, Luigi; Ledda, Caterina; Caputi, Antonio; Mansi, Francesca; Cannone, Enza Sabrina Silvana; Sponselli, Stefania; Cavone, Domenica; Birtolo, Francesco; Cannizzaro, Emanuele; Ferri, Giovanni Maria; Rapisarda, Venerando; Vimercati, Luigi (Frontiers in Public Health, 2020)
Port workers are exposed to a wide range of occupational hazards that can cause injuries and occupational diseases. Among these, exposure to benzene is one of the most important but least studied. The highest occupational exposures for port workers occur during the filling and loading of gasoline, and cleaning of tanks and receptacles. The aim of the study was to evaluate occupational exposure to low levels of benzene by measuring trans,trans-muconic acid (t,t-MA) in urine samples from workers operating at fuelling stations in a tourist port of Southern Italy. The overall sample was composed of 43 port workers of a tourist port in Southern Italy. In 2018, each participant provided two (morning and evening) urine samples for the determination of urinary t,t-MA. Urinary excretion of t,t-MA was always higher at the end of the work shift than at the beginning with significant difference (p = 0.002). In smokers, median t,t-MA urinary excretion is higher than non-smokers both at the beginning (90.5 μg/g creatinine vs. 61.45 μg/g creatinine) and at the end of the work shift (128.2 μg/g creatinine vs. 89.5 μg/g creatinine). Urinary excretion of t,t-MA is higher at the end of the work shift than at the beginning in both smokers and non-smokers, but the difference is significantly higher in non-smokers (p = 0.003) than in smokers (p = 0.05). In conclusion, our results showed that the role of inhaled benzene at fuelling stations in a tourist port can be relevant. On the basis of these results and the known adverse effects of benzene on human health, we encourage the use of personal protective equipment in the fuelling area of ports in order to minimize exposure to benzene to workers.